Ensuring uniformity of content and assessment in multi-section, on-site ESP university courses through ICT - Carlos Menéndez-Otero (Revista de Lenguas para Fines Específicos, 2019)
The paper presents an experience of use of ICT intended to overcome some of the problems currently plaguing ESP teaching at third level in Spain, namely student overcrowding, rising grade appealing, inadequacy and/or datedness of methodologies and syllabi, multi-campus lecturing, and disproportionate course management and assessment workload. The experience was developed in English for Commerce I, an on-site ESP required course in the curriculum of the BA in Commerce and Marketing currently taught at the University of Oviedo, during the first term of the year 2016/2017. The main aims were (1) to update the contents and methods of the course so that they allowed for significant, collaborative and autonomous learning of commercial English; (2) to significantly reduce the time the lecturers devoted to preparing, grading and reviewing tests, as well as handling student complaints, and (3) to greatly improve staff coordination so that uniformity of content and assessment could be guaranteed. The results show that aims (1) and (3) were fully met. As regards aim (2), even though ICT did reduce the time spent reviewing tests and handling complaints, the authors feel that the preparation of computer-assisted, on-site exams took longer than expected. Whereas the literature on the use of ICT in education mainly focuses on student motivation and engagement, the experience also bears out that ICT can be effectively used to combat student unhappiness by ensuring uniformity of content and assessment across sections in multi-section courses.